Platelet antibody production in children with congenital heart disease leading to coagulation dysfunction and reduced platelet function - ZHEN Zida; FU Xiaoyan; ZHANG Huimin; LIU Yu; MA Shuxuan (Zhongguo shuxue zazhi)
[Objective] To analyze the production of platelet antibodies in children with congenital heart disease, identify the types of antibodies, and explore their effects on platelet count, coagulation function and platelet function. [Methods] A retrospective analysis was conducted on 3 504 congenital heart disease patients without a history of blood transfusion who were treated at Beijing Children's Hospital between January 2019 and June 2024 to study the positive rate of platelet antibodies. Platelet antibody types were detected using the solid-phase agglutination method, and the platelet count and coagulation function of the children were analyzed. The impact of platelet antibodies on platelet function was evaluated using a coagulation and platelet function analyzer. [Results] The positive rate of platelet antibody in children with congenital heart disease with no history of blood transfusion was 9.7% (341/3 504), higher than the overall positive rate of 6.6% (2 657/40 311) in the general pediatric population. The platelet antibodies in congenital heart disease cases with positive platelet antibodies were mainly autoantibodies. There was no significant difference in platelet count between antibody-positive children and antibody-negative children. However, the prothrombin time (s) of antibody-positive children was significantly longer than that of antibody-negative children[(12.19±1.07) vs (11.32±0.77)]. Platelets sensitized by antibodies showed a significant reduction in function compared to non-sensitized platelets. [Conclusion] Children with congenital heart disease have a high rate of positivity for autoantibodies, which are associated with abnormalities in coagulation function and can lead to reduced platelet function.